Comparison of breathing models for determining flow and particle deposition in the lungs - King, Andrew; Mullins, Benjamin; Mead-Hunter, Ryan (Australasian Fluid Mechanics Society, 2012)
Collection and deposition of particles in the upper airway and lungs is of considerable importance – for example, when studying chronic diseases, or when determining the efficacy of aerosol drug delivery. Modelling of particle deposition usually assumes either constant flow (typically at maximum inspiration), or oscillating flow – ignoring any effects of the lung’s motion. This paper presents a preliminary examination of the effects of ignoring mesh motion when modelling the lungs. Initially, an idealised lung model was created, corresponding to generations 0 to 3 of Weibel’s morphology[14]. Simulations were then made using this geometry for steady flow, oscillating flow, and flow developed by expanding the lung. The expansion of the lung was modelled using a mesh motion library developed by the authors. This model allowed the expansion of the lung to be prescribed. Results from the simulations show significant differences between the three modelling options – relating to both the predicted flow field, and particle deposition sites. Robustness of the moving mesh modelling technique is demonstrated on a high-resolution geometry created from CT scans of a Sprague-Dawley rat model lung.